2020
DOI: 10.1108/rjta-08-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of using Trilobal® polyester on the functional performance of fencing suit

Abstract: Purpose The paper aims to use the Trilobal® polyester (Y cross-section) for producing fabrics suitable for fencing suits and evaluating their various properties. Design/methodology/approach Double weave structure was chosen to produce the samples by using six different face structures and two back structures divided into two groups according to the back structures. They were evaluated by their physical and mechanical properties such as tensile strength, puncture resistance, air permeability and humidity prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Fig. 7B shows that the 13 AC/T 0.4 sample of group 2 C gave the highest value of bursting strength, followed by the 23AC/T0.4 sample of group 2 C , due to the properties of the viscose as a regenerated material with the crystalline region for the sample 13 and the ratio of polyester fibers in sample 23 that characterized by its high strength [44].…”
Section: Bursting Strength Changes (%)mentioning
confidence: 95%
“…Fig. 7B shows that the 13 AC/T 0.4 sample of group 2 C gave the highest value of bursting strength, followed by the 23AC/T0.4 sample of group 2 C , due to the properties of the viscose as a regenerated material with the crystalline region for the sample 13 and the ratio of polyester fibers in sample 23 that characterized by its high strength [44].…”
Section: Bursting Strength Changes (%)mentioning
confidence: 95%
“…In the same context, many references stated that microfiber yarn cross-section shapes affect the surface and mechanical properties of fabrics [8,9]. Furthermore, references revealed that fibers movement within a cross-section of microfiber filaments Polyester microfiber yarns are one of the synthetic fibers that can be produced by many crosssections.…”
Section: Introductionmentioning
confidence: 99%